Distant metastasis of alveolar rhabdomyosarcoma with pancreatic parameningeal localization in children: clinical case series - A. D. Rodina; V. G. Polyakov; T. V. Gorbunova; O. A. Merkulov; A. L. Kashanina; A. A. Odzharova; A. M. Stroganova (Опухоли головы и шеи, 2023)
Rhabdomyosarcoma is a malignant neoplasm that develops from embryonic mesenchymal cells, with an annual incidence of 4.3 cases per 1,000,000 children. The prevalence of the tumor process is estimated on the basis of data from a comprehensive examination, including magnetic resonance imaging with intravenous contrast, ultrasound examination of the primary focus of regional and distant metastasis zones, computed tomography and radioisotope studies. The overall 5-year survival rate for localized rhabdomyosarcoma reaches 70 %. During the initial diagnosis, distant metastasis to the lungs, bones, and bone marrow is detected, which significantly worsens the prognosis in 20–25 % of patients. The factors of an extremely unfavorable prognosis for the course of alveolar rhabdomyosarcoma are the occurrence of regional and distant metastases before the start of specific treatment, dissemination of the tumor lesion during treatment, and the presence of translocation of the 13q14 sector. Publications contain data on a high (11.2 %) prevalence of metastases of alveolar rhabdomyosarcoma in the pancreas. In the presence of metastatic lesions of the pancreas, surgical treatment is effective only in combination with chemoradiotherapy. Long-term results of treatment of this cohort of children are unsatisfactory due to the high risk of recurrence and dissemination of the tumor.Aim. To study risk factors, evaluate methods and prospects for the treatment of children with metastatic pancreatic lesions in parameningeal alveolar rhabdomyosarcoma. The article considers three clinical cases of such a lesion. We would like to draw the attention of pediatric oncologists and radiologists to the possible association of metastases in the pancreas in children with localization of rhabdomyosarcoma in the head and neck region, which requires improvement of examination protocols in this group of patients.